2007
DOI: 10.2353/ajpath.2007.070285
|View full text |Cite
|
Sign up to set email alerts
|

Stromally Expressed c-Jun Regulates Proliferation of Prostate Epithelial Cells

Abstract: Stromal-epithelial interactions play a critical role inBenign prostatic hyperplasia (BPH) is the most common age-related proliferative abnormality of the human prostate affecting elderly men throughout the world. Half of all men have BPH identifiable histologically by age 60, and by age 85 the prevalence is ϳ90%. 1 The excessive cell proliferation associated with BPH causes benign prostatic enlargement, bladder outlet obstruction, and lower urinary tract symptoms, which afflict the patients. 2 BPH is a histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 63 publications
6
52
0
8
Order By: Relevance
“…These results suggested that the site of IGF-I may vary at different stage after castration; other studies also proved that the IGF-I synthesis may be different in certain circumstance and vary in different species. [15][16][17] In conclusion, we report here that although IGF-I of local VP decreases sharply in short-stage castration, its levels increase gradually and remain at high levels at least until 24 weeks after castration. IGF-I may act as a replacement for androgen by autocrine methods in the case of long-term castration.…”
Section: Igf-i Of Vp F Gao Et Alsupporting
confidence: 50%
See 1 more Smart Citation
“…These results suggested that the site of IGF-I may vary at different stage after castration; other studies also proved that the IGF-I synthesis may be different in certain circumstance and vary in different species. [15][16][17] In conclusion, we report here that although IGF-I of local VP decreases sharply in short-stage castration, its levels increase gradually and remain at high levels at least until 24 weeks after castration. IGF-I may act as a replacement for androgen by autocrine methods in the case of long-term castration.…”
Section: Igf-i Of Vp F Gao Et Alsupporting
confidence: 50%
“…3,14 IGF-I, one of the epithelial-stromal interaction factors, promotes prostate epithelial proliferation and anti-apoptosis through paracrine or autocrine way and is principally synthesized in prostate stroma or in the epithelium, or in both of these tissue compartments. [15][16][17] Previous study reported that IGF-I is synthesized mainly by stroma in short-stage castration, and may have a role through paracrine or autocrine way; 11 however, the sites of IGF-1 production in long-term castration (up to 24 weeks) is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…5B). Li et al (2007) have shown that c-Jun is abundantly expressed in the prostatic stroma but not in the epithelium of human BPH samples, and c-Jun is expressed at high levels in BPH nodules enriched with stroma. In the present study, positive correlations between K Ca 3.1 and c-Jun were significant in both implanted UGS and prostate needle biopsies from BPH patients (Figs.…”
Section: Discussionmentioning
confidence: 96%
“…The amplifying effect on c-Jun transactivation suggests that PAGE4 may modulate the activity of AP-1. Notably, c-Jun is also up-regulated in the developing (20) and diseased prostate (21)(22)(23)(24)(25)(26), whereas the AP-1 complex is up-regulated in symptomatic benign prostatic hyperplasia (27) as well as in prostate cancer (28). These patterns are coincident with PAGE4 expression (13) and underscore the importance of the PAGE4/c-Jun interactions in prostatic development and disease.…”
mentioning
confidence: 96%